Enhancing Tour Guiding Competencies through Simulation-Based Learning in Vocational Tourism Education - Uystka Hikmatul Kamiliyah NH; Vemas Aditia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
The simulation-based learning method is one way to train students to become skilled and professional tour guides in the future. Therefore, this study aims to analyze the effectiveness of simulation-based learning in enhancing students' tour-guiding competencies in the Tourism Destination study program at the State Polytechnic of Jember. This study employs a qualitative approach by collecting data through observation, in-depth interviews, and a literature review. The participants were 71 students enrolled in the course, from whom 10 were purposively selected as key informants based on their direct participation in simulation-based learning activities and their ability to provide rich, relevant information about their learning experiences. Data were analyzed using the Colaizzi technique, focusing on how students interpret their experiences during the simulation. The results reveal that simulation-based learning effectively enhances students' tour-guiding competencies by strengthening their communication, leadership, time management, and problem-solving skills while increasing self-confidence and emotional resilience. The learning experience also improves students' readiness to handle real-world professional situations by fostering teamwork, stress management, and workplace adaptability. Overall, the findings confirm that simulation-based learning, as a form of experiential learning, effectively develops cognitive, affective, and psychomotor competencies required of professional tour guides. Therefore, this approach should be integrated into the tourism curriculum to enhance students' work readiness and support practice-oriented learning.